Tourism : principles, practices, philosophies - Goeldner, Charles R (Wiley, 2015)
"The 12th Edition of Tourism: Principles, Practices, Philosophies explores major concepts in tourism, what makes tourism possible, and how tourism can become an important factor in the wealth of any nation. It is written in global terms, making it appropriate not only in the US but also for our subsidiary markets. It provides an overview of the principles, practices, and philosophies that affect the cultural, social, economic, psychological, and marketing aspects of human travel and the tourism industry. It looks at all aspects of the industry that serves travelers. The 12th Edition is an overall update of this leading comprehensive tourism text. Because the tourism industry changes so rapidly, the revision involves adding new developments, updating data, updating profiles, expanding some sectors, adding new web sites, adding selected references, and expanding the glossary. B & Bs, time share, meetings and conventions, sustainable tourism, climate change, social media, mobile marketing are some topics given expanded coverage in this new 12th Edition"--Provided by publisher.